THE RELATIONSHIP BETWEEN CHRISTIANITY AND SCIENCE: A BRIEF HISTORICAL STUDY ON DARWINISM AND THE DUTCH NEO-CALVINIST THEOLOGIANS - David Tong (STTRII, 2014)
The philosopher Ilse N. Bulhof's conclusion that the reception of Darwinism in the Netherlands was easy with opposition coming only from the religious quarters needs to be explained further. The fact is, opposition towards Darwinism came also from the academics and not all religious groups opposed it. The modern liberal accepted Darwinism without much reservation. Two great figures of the Dutch neo-Calvinisme, Abraham Kuyper and Herman Bavinck, accepted evolution as a fact while rejecting Darwinism. Bulfhof's conclusion above should not be understood as a conflict between faith and science. The real conflict is not between faith and science, but between two diametrically opposing worldviews. This is the reason why not all scientists embraced Darwinism. It is interesting to observe that the second generation of the Dutch neo- Calvinsm (Valentine Hepp, for example) resisted all forms of evolution theories. Several possible reasons explaining the discontinuity between these two generations of neo-Calvinism will also be given in this paper.?